Right ventricular fibrosis in adults with uncorrected secundum atrial septal defect and pulmonary hypertension: a cardiovascular magnetic resonance study with late gadolinium enhancement, native T1 and extracellular volume - Ginting Munte, Fatwiadi Apulita; Elen, Elen; Lelya, Olfi; Rudiktyo, Estu; Prakoso, Radityo; Lilyasari, Oktavia (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Right ventricular (RV) fibrosis represents both adaptive and maladaptive response to the overloaded RV condition. Its role in pulmonary hypertension (PH) associated with secundum atrial septal defect (ASD), the most common adult congenital heart disease (CHD), remains poorly understood. Methods: We enrolled 65 participants aged ³18 years old with uncorrected secundum ASD who had undergone clinically indicated right heart catheterization (RHC) which divided into non-PH group (n=7), PH group (n=42) and Eisenmenger syndrome (ES) group (n=16). We conducted cardiovascular magnetic resonance (CMR) studies with late gadolinium enhancement (LGE) imaging, native T1 and extracellular volume (ECV) measurement to evaluate the extent and clinical correlates of RV fibrosis. Results: Late gadolinium enhancement was present in 94% of population, including in 86% of non-PH group, mostly located at the right ventricular insertion point (RVIP) regions. LGE in the septal and inferior RV region was predominantly observed in the ES group compared to the other groups (p = 0.031 and p <0.001, respectively). Mean LGE scores in ES and PH groups were significantly higher than non-PH group (3.38 ± 0.96 vs. 2.74 ± 1.04 vs. 1.57 ± 0.79; p = 0.001). ES and PH group had significantly higher degree of interstitial RV fibrosis compared to non-PH group, indicated by native T1 (1199.9 ± 68.9 ms vs. 1131.4 ± 47.8 ms vs. 1105.4 ± 44.0 ms; p <0.001) and ECV (43.6 ± 6.6% vs. 39.5 ± 4.9% vs. 39.4 ± 5.8%; p = 0.037). Additionally, native T1 significantly correlated with pulmonary vascular resistance (r = 0.708, p < 0.001), RV ejection fraction (r = -0.468, p <0.001) and peripheral oxygen saturation (r = -0.410, p = 0.001).In uncorrected secundum ASD patients, RV fibrosis may occur before the development of PH, and progressively intensifies alongside the progression of PH severity. Higher degree of RV fibrosis, derived from CMR imaging, correlates with worse hemodynamic, RV dysfunction, and poorer clinical condition.